Use of T-Tube Enterostomy in Neonatal Gastro-intestinal Surgery - Maher Al-zaiem; Abdulhadi F. AL-Garni; Abdulrahman Almaghrebi; Asim A. Asghar (EL-Med-Pub, 2020)
Aim: To evaluate the results of the use of the T-tube ileostomy in neonatal intestinal surgery cases. Materials and Methods: A retrospective review of sixty two neonates underwent intestinal obstruction surgery by using T-tube ileostomy was conducted between January 1990 and January 2013.The pathologies of the intestinal obstruction were; thirty four of jejunoileal atresia cases, thirteen case meconium ileus, eight cases perforated necrotizing enterocolitis (NEC), three cases meconium peritonitis, three cases with bowel resection due to intestinal volvulus, and one case of gastroschisis. Results: Mean duration of T-tube placement was 13 days (range9-20days) and the sites of T-tube insertion closed spontaneously in 2 days (range 1-4 days). The mean duration for starting oral intake postoperatively in these patients was 9 days (6-16 days). All patients well tolerated the procedure and there were no serious complications related to the T-tube insertion. However, four patients died due to other reasons like sepsis, respiratory failure and prematurity. Conclusion: T-tube enterostomy is an effective and safe technique for treatment of selected cases of neonatal intestinal surgery. It showed less morbidity and mortality rates than the conventional stoma. Therefore, it is considered a helpful approach in cases where there is danger of hypoperistaltic dilated bowel proximal to the anastomosis.